2007
DOI: 10.1002/clc.2
|View full text |Cite
|
Sign up to set email alerts
|

Association of platelet‐monocyte aggregates with platelet activation, systemic inflammation, and myocardial injury in patients with non‐st elevation acute coronary syndromes

Abstract: SummaryBackground: Platelet-monocyte aggregates (PMA) and C-reactive protein (CRP) are increased in unstable coronary disease. The interrelation of PMA with platelet activation, systemic inflammation, and their association with markers of myocardial injury has not been studied extensively.Hypothesis: The study was undertaken to evaluate the association of CRP, PMA, and cardiac troponin I (cTnI) in patients admitted with non-ST elevation acute coronary syndromes (NSTE-ACS).Methods: In all, 69 consecutive patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
49
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 20 publications
2
49
1
2
Order By: Relevance
“…In previous studies, high monocyte count was shown to be significantly associated with cardiovascular prognosis including mortality in STEMI [11,12]. Increased circulating platelet-monocyte aggregates were observed in patients with acute coronary syndromes [13,14], which could induce expression and release of chemotactic factors, including monocyte-chemoattractant-protein-1 (MCP-1) and interleukin-8 (IL-8) from monocytes [15]. Besides activation of monocyte adhesion onto endothelial cells, MCP-1 induces the expression of tissue factor, superoxide anions, and exerts prothrombotic effects [16,17].…”
Section: Discussionmentioning
confidence: 93%
“…In previous studies, high monocyte count was shown to be significantly associated with cardiovascular prognosis including mortality in STEMI [11,12]. Increased circulating platelet-monocyte aggregates were observed in patients with acute coronary syndromes [13,14], which could induce expression and release of chemotactic factors, including monocyte-chemoattractant-protein-1 (MCP-1) and interleukin-8 (IL-8) from monocytes [15]. Besides activation of monocyte adhesion onto endothelial cells, MCP-1 induces the expression of tissue factor, superoxide anions, and exerts prothrombotic effects [16,17].…”
Section: Discussionmentioning
confidence: 93%
“…Platelet-leukocyte complex assessed by flow cytometry has been found as a pathophysiologic mechanism for the development of thrombogenesis [6], and monocyte-platelet aggregation was also shown as an early marker for acute MI [28] and NSTE-ASC patients [30]. Rinder et al [5] showed that this cellular interaction is a dynamic process, in which platelet activation status and the ability of leukocytes to adhere result in different bindings.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating CRP levels on admission have been shown to be elevated in AMI patients. 2,3) The increase in CRP levels in these patients has been mainly explained by the stimulating effects of myocardial damage and necrosis on systemic inflammatory response. 27) However, there are also studies suggesting that elevated CRP levels in AMI patients may result from inflammation caused by the plaque rupture.…”
Section: Discussionmentioning
confidence: 99%
“…1) It has been demonstrated in acute myocardial infarction (AMI) patients that admission levels of plasma C-reactive protein (CRP), which is a sensitive inflammatory marker, are elevated 2,3) and associated with short-and long-term outcomes, [2][3][4][5] including the occurrence of heart failure (HF) during the hospitalization period. 6) Moreover, inflammatory processes have also been suggested to play a role in the pathogenesis of cardiogenic shock (CS) complicating AMI.…”
mentioning
confidence: 99%
See 1 more Smart Citation